2017
DOI: 10.15171/ajmb.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant capacity, lipid peroxidation, thiol group and catalase activity in patients with kidney stone

Abstract: Background: Urinary tract stones are one of the most common causes of kidney disease. There is evidence for the possible involvement of oxidative stress in the formation of kidney stones and renal cell injury. Objectives: In this study, we aimed to determine the total antioxidant capacity (TAC), malondialdehyde (MDA), serum thiol group, ceruloplasmin (CP) levels and catalase (CAT) activity in the serum of the patients with kidney stones. Materials and Methods: This study was conducted as a case-control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, the results obtained by Rostampour et al 65 showed that MDA levels were higher in the subjects with kidney stones compared to the healthy subjects, though this increase was not significant. Finally, reactive oxygen species (ROS) were known to perturb the oxidant‐antioxidant balance in kidney cells, resulting in cellular damage 67 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the results obtained by Rostampour et al 65 showed that MDA levels were higher in the subjects with kidney stones compared to the healthy subjects, though this increase was not significant. Finally, reactive oxygen species (ROS) were known to perturb the oxidant‐antioxidant balance in kidney cells, resulting in cellular damage 67 .…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, the kidneys were potentially exposed to high concentrations of oxidants and reactive electrophiles. As well, Rostampour et al 65 stated that oxidative stress caused the reduction of GSH. Likewise, Carrasco‐Valiente et al 66 reported that LPO was significantly higher in the subjects with kidney stones compared to the subjects without kidney stones.…”
Section: Discussionmentioning
confidence: 98%
“…The assay principles were based on the reaction of catalase to decompose hydrogen dioxide. According to the kit instructions (Kiazist, Iran), samples were mixed with buffer assay (hydrogen peroxide) and the reduction of absorbance as a result of hydrogen peroxidase elimination were recorded at 240 nm ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The level of GSH, as a main antioxidant parameter in the body, was evaluated in the sera of experimental mice, using Ellman's method with minor modification (Rostampour et al, 2017). The process was based on the formation of GS-TNB complex from DTNB (5, 5' dithiobis 2-nitrobenzoic acid) which developed yellow color because of the DTNB reduction.…”
Section: Determination Of Antioxidant Statementioning
confidence: 99%